Cancer-derived exosomic microRNAs shape the immune system within the tumor microenvironment: State of the art. (July 2017) - Fanini, Francesca; Fabbri, Muller
Abstract: In recent years there has been an increasing interest of the scientific community on exosome research, with particular emphasis on the mechanisms by which tumor-derived exosomes can promote tumor growth. Particularly, exosome-mediated immune-escape is under deep investigation and still represents a quite controversial issue. Tumor-derived exosomes are carriers of information able to reprogram functions of immune target cells, influencing their development, maturation, and antitumor activities. They deliver proteins similar to those of the parent cancer cells, but also genetic messages like genomic DNA, mRNA, and microRNAs (miRNAs) that ultimately share the so called "tumor microenvironment" in a pro-tumoral fashion. The content of tumor-derived exosomes could be implicated in several signaling pathways operating in the tumor microenvironment, providing a further modality of dys-regulation of antitumor immunity. The aim of this review is to provide a state-of-the-art highlight of to the most recent discoveries in the field of interaction between tumor-derived exosomic miRNAs and the cells of immune system.